Pengaruh kepemilikan institusional, risiko bisnis, kualitas audit, ketepatan waktu pelaporan keuangan, dan struktur modal terhadap nilai perusahaan - Azzahra, Vivi Fachrani; Saphira, Janice; Astuti, Christina Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Company value is an information or benchmark of a company seen from the company's stock price level. this makes every company vying to increase the value of the company that is sought in order to attract investors. Because high values indicate that the situation is good and shows the prosperity of the company owners. The purpose of this research is to obtain empirical evidence about the factors that affect firm value in primary consumer manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The factors used include institutional ownership, business risk, audit quality, timeliness of financial reporting, and capital structure. This study uses 87 primary consumer manufacturing companies listed on the Indonesia Stock Exchange as the population. In sampling, this study uses purposive sampling method, so as to obtain 58 primary consumer manufacturing companies listed on the Indonesia Stock Exchange as a population. This research uses multiple linear analysis method. So get the results of research which states that business risk, audit quality, and capital structure have a positive effect on firm value. While institutional ownership and timeliness of financial reporting have no effect on the company.